On-demand, In-place Help for Augmented Reality Environments - Tan, Desney; Poupyrev, Ivan; Billinghurst, Mark; Kato, Hirokazu; Regenbrecht, Holger; Tetsutani, Nobuji ((2001) Poster at Ubicomp 2001, 2001)
In many help systems, users are either distracted with a constant barrage of help or have to stop working on the task at hand and explicitly search for help. In this paper, we propose two methods to present on-demand, in-place help in augmented reality environments. In the interfaces we describe, users interact with virtual objects that are superimposed on the real world by manipulating physical cards. We describe Tiles, a prototype application for designing aircraft instrument panels, from which our work on help systems grew. In Tiles, users manipulate special ‘help’ cards in combination with data cards to invoke detailed help. This technique, which we call Tangible Bubble Help may be multi-modal, taking the form of text, audio, graphics, and animations. We also present Tangible Tooltips, a lightweight technique in which users control the display of textual help by tilting data cards. In both cases, users can seamlessly transition between performing the main task and acquiring help.